Patient-centred care - preanalytical factors demand attention: A questionnaire study of venous blood sampling and specimen handling - Wallin, O.; Söderberg, J.; Van Guelpen, B.; Brulin, C.; Grankvist, K. (Scandinavian journal of clinical and laboratory investigation, 2007)
Objective. Most mistakes in laboratory medicine are the result of human error occurring before the blood sample reaches the laboratory. This survey of preanalytical procedures was designed to identify sources of error and potential targets for quality improvement strategies. Material and methods. The staff in a highly specialized surgical ward at a university hospital completed a questionnaire addressing the collection and handling of venous blood samples in plastic vacuum test-tubes for general clinical chemistry testing. Results. The results suggest that venous blood sampling instructions are not always followed. When uncertain about how a sample should be collected, the majority of respondents rely on potentially poor sources of information, such as out-of-date printed instructions or the advice of a colleague, rather than consult up-to-date electronic instructions. Furthermore, they do not always report errors and the referrals are not always handled according to sampling instructions. The respondents were highly motivated, however, and had a strong interest in receiving further education in, and assuming increased responsibility for, venous blood sampling procedures in the ward. Conclusions. We believe that the introduction of standardized routines and regular staff training, combined with an exchange of the existing paper-based referral management system with an electronic system for managing referrals, could increase safety in the preanalytical process, with positive effects on patient safety. Given the importance of venous blood samples in patient care, a more extensive study covering other hospital wards and primary health-care centres is needed.